Optimalisasi Kebijakan Hukum Dan Inovasi Teknologi Untuk Mewujudkan Swasembada Pangan Berkelanjutan - Taryani Kesumawardani; Siti Hamimah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Food is a basic human need guaranteed in the 1945 Constitution and is also regulated in Law Number 18 of 2012 concerning Food. Food-related challenges in Indonesia are still a major issue that requires serious attention, considering the increase in global food demand which is estimated to reach 70% by 2050 (FAO). Therefore, effective innovation and policies are needed to ensure the availability of quality and sustainable food. This research uses normative methods, with a legislative and conceptual approach to understand the laws related to food self-sufficiency. In addition to the Food Law, other regulations such as Law Number 11 of 2020 concerning Job Creation are also relevant legal basis. Sustainable food self-sufficiency is the government's commitment to realize food sovereignty and security in accordance with the mandate of the 1945 Constitution and the 2nd SDGs global agenda (Zero Hunger). Cooperation between consistent legal policies, technological innovations such as precision agriculture, and natural resource protection are key to achieving this goal. With strategic steps, Indonesia can realize food self-sufficiency that prospers the community and contributes to world food security. Keywords: optimization of law, sovereignty, food self-sufficiency.